Analisis Peningkatan UMKM Proses Pengolahan Dan Pemasaran Singkong Melalui Kegiatan Sosialisasi Bersama Pemdes Balai Pungut - Yesi Yesi; Dyra Vania; Alvina Damayani; Dewi Fortuna BR Tarigan; Ahmad Rafli; Ola Noviza; Salsabila Putri Roshen; Miftahul Jannah; Nanda Marela; Hanifa Safitri (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
MSMEs are activities in the business sector that are managed by individuals or small business entities, so they can have an impact on the economy. The role of MSMEs in the economic growth of Indonesian society is very influential. Based on these observation activities, the problem was found that MSMEs in Pungut Village, Pinggir, Bengkalis have opportunities in the MSME sector but have not been able to develop MSMEs into a source of income for the surrounding community. Through this presentation, KUKERTA students contributed in the form of implementing work programs related to the processing and marketing of cassava in Pungut Village, Pinggir, Bengkalis. The aim of carrying out this activity is to analyze the improvement of MSMEs in the Process of Cassava Processing and Marketing through outreach activities with the Balai Pungut Village Government. The implementation method was carried out in Pungut Village, Pinggir, Bengkalis. Socialization activities to raise the potential of Balai Pungut Village through cassava and developing MSMEs for PKK mothers were carried out on August 10 2023. Kukerta activities carried out in Pungut Village went smoothly. This can be done well due to several factors such as the enthusiasm of the good community and the high solidarity of Kukerta students. The new innovation discovered by Kukerta students based on community service activities carried out in Pungut Village is developing the MSME business of the Pungut Village Community through the discovery of processed products made from cassava, namely cassava nuggets.